A novel early strength agent prepared by wet-grinding concrete waste slurry and its effect on early hydration and mechanical properties of cement based materials. (2nd January 2023) - Su, Ying; Wu, Lei; He, Xingyang; Zheng, Zhengqi; Tan, Hongbo; Yang, Jin; Ma, Qinghong; Ding, Jingjing; Bao, Ming
Highlights: The particle size of CWS after wet-grinding decreased (D50 = 0.7 μm) and the pH value increased. The CSH gel of CWS increased after wet-grinding. The addition of CSW has significantly improved the early hydration rate of cement-based materials. Abstract: Adding nano particles were supposed to displace steaming curing in manufacturing prefabricated components of concrete for avoiding thermal damage. Nevertheless, there were not yet appropriate nano particles adapted for practical production, and the main reason was those existing nano particles involved complicated technological processes and high costs. Last incompatibility with cement-based materials confined to its application. In this study, a new early strength agent was prepared by wet-grinding concrete waste slurry (CWS). The physicochemical properties of CWS after wet-grinding were analyzed by means of XRD, the particle size distribution (PSD), ICP, SEM, pH, resistivity, and TG. Finally, the effects of CWS on the early hydration processes and mechanical properties of cement-based materials were explored by means of setting time, hydration heat, chemical shrinkage, resistivity, mechanical properties, and MIP. The results showed that the particle size of CWS after wet-grinding decreased (D50 = 0.7 μm). Meanwhile, the surface area and the dissolution of alkaline ions in the solution increased, which provided nucleation sites and the alkaline environment for the early hydration of cement-based materials. Moreover, the early hydration rate of cement and mechanical properties were greatly improved. For instance, the cumulative heat release at 12 h increased by 111.7%, the induction period was shortened, the gel hole increased by 8% in 12 h, the large hole decreased by 37%, and the initial and final coagulation time was shortened by >30%, the compressive strength at 12 h increased by 406.3%, and the compressive strength was basically equivalent in the later period. The research in this paper showed that it was feasible to prepare the new early strength agent from CWS through the wet-grinding treatment, which provided a new reference for the green development of the prefabricated component industry.